Prospects for the development of corporate social responsibility in Poland after the COVID-19 pandemic - Kubiczek, Jakub (The journal of contemporary issues in business and government, 2021)
The outbreak of the COVID-19 pandemic raised many questions, including these concerning the future of CSR. The aim of this study is to present the prospects for the development of corporate social responsibility in Poland after the COVID-19 pandemic. The number of good practices in Poland is increasing every year and the dynamics was maintained during the pandemic, despite the fact that some sectors faced a difficult economic situation. Special attention should be paid to enterprises that are financed with public money, as they were the ones that started activities for the benefit of local communities during the pandemic. The post-pandemic period will ensure the stabilization of the economic situation and may constitute the foundation for the further development of corporate social responsibility.